2017
DOI: 10.1111/jcpe.12694
|View full text |Cite
|
Sign up to set email alerts
|

Short dental implants (6 mm) versus long dental implants (11–15 mm) in combination with sinus floor elevation procedures: 3‐year results from a multicentre, randomized, controlled clinical trial

Abstract: Within the limitations of this study, implants with a length of 6 mm as well as longer implants in combination with a lateral sinus lift may be considered as a treatment option provided a residual ridge height of 5-7 mm in the atrophied posterior maxilla is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
143
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(148 citation statements)
references
References 20 publications
(30 reference statements)
4
143
0
1
Order By: Relevance
“…39 Table 2 shows the characteristics of the four studies included in this systematic review, of which three were RCTs and one was a CCT. 70,71 The study by Rossi et al 40 evaluated implants in both arches as well as the study of Mendoza-Azpur et al, 39 but the latter did not specify the exact number of implants in each arch and in each group. Two studies evaluated implants only in the maxilla.…”
Section: Search and Analysis Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Table 2 shows the characteristics of the four studies included in this systematic review, of which three were RCTs and one was a CCT. 70,71 The study by Rossi et al 40 evaluated implants in both arches as well as the study of Mendoza-Azpur et al, 39 but the latter did not specify the exact number of implants in each arch and in each group. Two studies evaluated implants only in the maxilla.…”
Section: Search and Analysis Of Studiesmentioning
confidence: 99%
“…The study by Guljé et al70 with a one-year follow-up obtained the study by Pohl et al71 reported the presence of prosthetic failures; there were eight loosenings of abutments screw and two decementations of crowns in the short implants, and two loosenings of abutments and one decementation of crown in standard implants.The study by Pohl et al71 reported a buccal fistula and pronounced hematoma in the group of standard implants with bone graft.4 | DISCUSSIONThe main objective of this systematic review was to compare the survival rate of short implants relative to standard implants in posterior single crowns. The control implant was lost during the first year.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Although systematic reviews corroborate favourable clinical outcomes following bone augmentation procedures for dental implant fixation in the posterior maxilla controversy still involves the most effective or preferred protocol(s) (Del Fabbro, Wallace, & Testori, ; Esposito, Felice, & Worthington, ; Lundgren et al., ; Pjetursson, Tan, Zwahlen, & Lang, ; Tan, Lang, Zwahlen, & Pjetursson, ). This conundrum primarily revolves around the choice of autogenous bone grafts, synthetic or cadaver‐sourced bone biomaterials, biologic amplifiers or any combination thereof but also surgical approach and implant technology; short implants advocated to at all evade augmentation procedures (Al‐Nawas & Schiegnitz, ; Esposito et al., ; Pohl et al., ). Moreover, a recent review suggests that: “The mere elevation of the maxillary sinus membrane and the simultaneous placement of implants results in bone formation and osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies over the past few years have proved the possibility of short implant placement and have confirmed its clinical effectiveness in comparison with the conventional treatment with sinus augmentation [5][6][7]. It was stated that the use of short implants might avoid adjunct procedures used for implant insertion, thereby reducing operative time, complexity and postoperative discomfort [8].…”
Section: Introductionmentioning
confidence: 99%